Lansekap Mini: Menggali Potensi Ekonomi dan Kreativitas Pemuda Gampong Kahju dalam Menghadapi Tantangan dan Peluang Industri Kreatif - Zulfikar Taqiuddin; Irzaidi Irzaidi; Zahriah Zahriah; Rahmi Sofyan; Iin Sabrina Hilal (Universitas Syiah Kuala, 2026)
The creative economy sector offers a viable solution to the high rates of school dropouts and youth unemployment in Gampong Kahju, Aceh Besar. This community service initiative is driven by a lack of productive skills among local youth, contrasted by the surging demand for green interior elements in urban Banda Aceh. The program aims to transform the vocational skills of school dropouts through training in mini-landscape (terrarium) production as an innovative decorative product. The methodology encompasses three key stages: providing entrepreneurial motivation, technical guidance in integrated sculpture-based landscape design, and market trend analysis. The results demonstrate a significant increase in the participants' creative capacity and mastery of aesthetic techniques. However, evaluations highlight the need for quality standardization through visual modules, production efficiency using simple mechanical tools, and the optimization of waste-based materials to ensure production independence. Regarding sustainability, future strategies will focus on digital marketing, the establishment of Joint Business Groups (KUB), and product diversification through technology integration, such as smart lighting. By fostering strategic partnerships with the retail industry, this program is projected to create a competitive and sustainable young entrepreneurial ecosystem within the creative industry.